Using the Sonogashira Reaction for Preparing a New Fragment Library based on the 3-alkynylimidazo[1,2-a]pyridine Scaffold - Castera-Ducros, Caroline; El-Kashef, Hussein; Piednoel, Melanie; Remusat, Vincent; Teulade, Jean-Claude; Verhaeghe, Pierre; Rathelot, Pascal; Vanelle, Patrice (Letters in Organic Chemistry, 2016)
Background: The imidazo[1,2-a]pyridine ring has been widely studied by medicinal chemists and displays great pharmaceutical potential. Methods: In a view to prepare a library of new molecules including an imidazo[1,2-a]pyridine scaffold, as original fragments for the conception of novel anti-protozoal compounds, the Sonogashira crosscoupling reaction between 3-halogenoimidazo [1,2-a]pyridines and phenylacetylene was studied. Results: From 3-iodoimidazo[1,2-a]pyridine, chosen as an optimal substrate for conducting the reaction at room temperature in 2 hours, a variety of terminal alkynes was involved into the reaction, leading to a series of 16 new 3-phenyethynylimidazo [1,2-a]pyridines in satisfying to good yields (50-82%) and 4 additional derivatives in moderate yields (30-40%). Conclusion: Such synthetic approach appears efficient for the rapid synthesis of imidazopyridine chemical libraries. The corresponding derivatives will next be evaluated for their anti-infective properties.
Keywords: 2-a]pyridines